Strategies on technology management for coffee smallholder to promote the smart farming implementation. Issue 1 (May 2021) - Wulandari, S; Ferry, Y
Abstract: Smart farming is becoming increasingly important in providing technology infrastructure for the coffee agribusiness to develop a competitive value chain. On the other side, most coffee smallholders are characterized by limited access to technology and low technology adoption. As development and exploitation of technological capabilities, technology management would be a strategic way to promote smart farming implementation. Hence, this study aims twofold: (1) to identify the constraints in smart farming implementation, and (2) formulate technology management strategy in supporting smart farming for the coffee smallholder. The study was conducted in West Lampung, and the analysis method used pairwise comparison by using Saaty's scale. The analysis reveals that respondents' constraints related to knowledge and skills, technology, information, capital, organizational, and resources aspects. The results of this study provide useful information about technoware, humanware, inforware, orgaware, and cysnetware, as components of technology management, to support smart farming for the coffee smallholder.